Between walls: the gipsies house (2021)
In this text is described the proposal presented for the contest of the new Home for the Gipsy Brotherhood, in Seville, Spain. This proposal commences by recognizing the limit as a tension between the inside and outside, determining their spatial and formal setting. In the project idea, the particularities present discontinuities in the tension between the city and the buildings, with the presence of a wall that contains the external space and the thick walls of the church, which emphasize the internal space control. This discussion raises two considerations structuring the architectural proposals: building the boundary and expanding the interior.